(untitled) - Dorsey, Alan H. (Hoboken, N.J., 2007)
This book covers all of the key alpha sources currently mined by active managers, reduces the complexity of the subject, and helps the investor get started in the right direction
Keywords: Portfolio management,Investments,Factor analysis,Quản trị đầu tư